2002
DOI: 10.1161/01.str.0000024432.34557.10
|View full text |Cite
|
Sign up to set email alerts
|

Is Mild Cognitive Impairment Prodromal for Vascular Dementia Like Alzheimer’s Disease?

Abstract: Background and Purpose-Individuals with mild cognitive impairment (MCI) are at increased risk of Alzheimer's disease (AD) and probably other forms of dementia. Some subtypes of vascular dementia (VaD) may possess minor neuropathological changes of AD that may contribute to cognitive impairments. It was posited that MCI, identified by criteria described here, might present as a prodrome for VaD and AD. Methods-Serial Mini-Mental State Examination was administered at 3-to 6-month intervals, and neuroimaging was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
134
0
12

Year Published

2002
2002
2013
2013

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 182 publications
(154 citation statements)
references
References 51 publications
8
134
0
12
Order By: Relevance
“…Lopez et al (2007) have, indeed, rightly noted that when the subject's cognitive deficits could be due to nondegenerative conditions (such as a small-vessel subcortical pathology), a greater proportion of MCI patients remain cognitively stable or return to a normal baseline. These reasons could contribute to explain the conflicting results of previous studies dealing with the patterns of cognitive impairment observed in VD and DAT patients (e.g., Desmond, 2004;Laukka et al, 2004;Looi & Sachdev, 1999;Meyer et al, 2002;Reed et al, 2007). It is also possible that the absence of a clear neuropsychological pattern in vascular MCI patients was due to their small sample size (and hence to insufficient statistical power ) but this hypothesis is at variance with the fact that a clear and consistent neuropsychological pattern was found in the even smaller group of atrophic MCI patients.…”
Section: Discussionmentioning
confidence: 96%
“…Lopez et al (2007) have, indeed, rightly noted that when the subject's cognitive deficits could be due to nondegenerative conditions (such as a small-vessel subcortical pathology), a greater proportion of MCI patients remain cognitively stable or return to a normal baseline. These reasons could contribute to explain the conflicting results of previous studies dealing with the patterns of cognitive impairment observed in VD and DAT patients (e.g., Desmond, 2004;Laukka et al, 2004;Looi & Sachdev, 1999;Meyer et al, 2002;Reed et al, 2007). It is also possible that the absence of a clear neuropsychological pattern in vascular MCI patients was due to their small sample size (and hence to insufficient statistical power ) but this hypothesis is at variance with the fact that a clear and consistent neuropsychological pattern was found in the even smaller group of atrophic MCI patients.…”
Section: Discussionmentioning
confidence: 96%
“…One of the most prevalent subtypes (36-67%, according to different authors), the subcortical ischemic vascular disease (SIVD), is due to gradually progressive microvascular changes that might cause insidious and subtle cognitive impairments before diagnostic of VaD becomes established. Most (83.3%) subcortical small-vessel dementias might exhibit prodromal MCI, similar to what occurs in Alzheimer's disease (AD) 5 . On magnetic resonance imaging (MRI), SIVD usually appears as periventricular and deep white-matter signal hyperintensities (WMHs), visible on T2 and FLAIR images, and lesions in the prefrontal subcortical circuits are known to be involved in executive function, including control of working memory, organization, language, mood, regulation of attention, and constructional skills 3 .…”
mentioning
confidence: 77%
“…To date, diagnostic criteria developed to characterize cognitive syndromes associated with vascular disease require evidence of CVD or stroke previous to cognitive impairment, focal signs on physical examination, fluctuating stepwise course or dementia onset within three months of a stroke 4 . Although the need for a temporal association between stroke and cognitive changes may be relevant in cases of post-stroke dementia, it does not apply to cases of SIVD, in which cognitive decline may be slowly progressive rather than stepwise 5 . Therefore, diagnostic criteria for VCI due to SIVD should embrace cognitive impairments associated to deep white matter changes.…”
mentioning
confidence: 99%
“…Diversos estudos mostram que portadores de CCL apresentam maior risco de desenvolver quadros demenciais (Meyer et al, 2002;Sarazin, Dubois, 2002;Lopez, Dekoski, 2003). Cerca de 10 a 15% desses idosos tendem a apresentar a doença de Alzheimer em um ano, o que ressalta a importância da identificação desses casos.…”
Section: Discussão Dos Resultados Encontrados Na Avaliação Cognitivaunclassified